Genome‐wide transcriptomic analyses provide insights into the lifestyle transition and effector repertoire of Leptosphaeria maculans during the colonization of Brassica napus seedlings. (3rd May 2016) - Haddadi, Parham; Ma, Lisong; Wang, Haiyan; Borhan, M. Hossein
Summary: Molecular interaction between the causal agent of blackleg disease, Leptosphaeria maculans ( Lm ), and its host, Brassica napus, is largely unknown. We applied a deep RNA‐sequencing approach to gain insight into the pathogenicity mechanisms of Lm and the defence response of B. napus . RNA from the infected susceptible B. napus cultivar Topas DH16516, sampled at 2‐day intervals (0–8 days), was sequenced and used for gene expression profiling. Patterns of gene expression regulation in B. napus showed multifaceted defence responses evident by the differential expression of genes encoding the pattern recognition receptor CERK1 (chitin elicitor receptor kinase 1), receptor like proteins and WRKY transcription factors. The up‐regulation of genes related to salicylic acid and jasmonic acid at the initial and late stages of infection, respectively, provided evidence for the biotrophic and necrotrophic life stages of Lm during the infection of B. napus cotyledons. Lm transition from biotrophy to necrotropy was also supported by the expression function of Lm necrosis and ethylene‐inducing (Nep‐1)‐like peptide. Genes encoding polyketide synthases and non‐ribosomal peptide synthetases, with potential roles in pathogenicity, were up‐regulated at 6–8 days after inoculation. Among other plant defence‐related genes differentially regulated in response to Lm infection were genes involved in the reinforcement of the cell wall and the production of glucosinolates. Dual RNA‐sequencing allowed us to define the Lm candidate effectors expressed during the infection of B . napus . Several candidate effectors suppressed Bax‐ induced cell death when transiently expressed in Nicotiana benthamaina leaves.